Molecular detection of Pneumocystis jirovecii using polymerase chain reaction in immunocompromised patients with pulmonary disorders in northeast of Iran - Mahmood Parian; Abdolmajid Fata; Mohammad Javad Najafzadeh; Fariba Rezaeitalab (Mazandaran University of Medical Sciences, 2015)
Background and Purpose: Pneumocystis pneumonia, caused by Pneumocystis jirovecii, is a fatal disease threatening patients with AIDS or immunosuppression. Assessment of colonization in these patients is of great significance, since it can lead to severe pulmonary disorders. Considering the scarcity of published reports on Pneumocystis jirovecii isolates from patients in Mashhad, Iran, we aimed to evaluate pneumocystis colonization in individuals with different pulmonary disorders. Materials and Methods: We used nested polymerase chain reaction (PCR) method to amplify mitochondrial large subunit-ribosomal ribonucleic acid (mtLSU-rRNA) gene in 60 bronchoalveolar lavage (BAL) samples, obtained from patients, referring to the Department of Internal Medicine (Pulmonary Diseases Section) at Imam Reza Hospital, affiliated to Mashhad University of Medical Sciences, Mashhad, Iran. Results: DNA of Pneumocystis jirovecii was detected in 10 out of 60 BAL samples (16.66%) via nested PCR method. Conclusion: According to the present findings, the colonization rate of Pneumocystis jirovecii was similar to the rates reported in other similar studies in Iran.